Concentração de macro e micronutrientes em áreas úmidas de chapada no município de Uberlândia/MG - Ferreira, Daniele Araújo (2015)
Expansion and intensification are two ways to increase agricultural productivity nevertheless both cause environmental impacts. In Triangulo Mineiro Cerrado, agriculture expansion and the intensification started in the 1970s have occupied initially the Oxisols areas, but the need for more land for cultivation exceeded its limits and advanced or incorporated wetlands of field mounds. Mounds fields correspond to topographic depressions located on the surface of the sedimentary plateau and they are ecosystems are ecosystems that remain temporarily or permanently flooded. They have organic matter rich soils overlapping light gray or mottled mineral horizon reflecting the conditions of iron oxide reduction in flooded environments. Such areas are not scheduled and the Brazilian Forest Code has not considered them as wetlands. Furthermore, they have no specific legislation concerning to permanent preservation areas factor that hinders the inhibition of advancing agriculture at its edges. This is due to intrinsic features regarding soil, topography as well the presence of the high water level. So, this study aimed to evaluate the agriculture impacts on mounds fields by comparison between the macro contents (N, P, K, Ca, Mg, S) and micronutrients (Fe, Mn, Cu, Zn) in a drained mound used in cultivation and another not impacted one used as control soil. We collected samples at three depths and carried out morphological and grain size analysis in the complex sorption in order to compare both environments. The results showed that we could characterize mounds as areas for nutrient interception released in fertilizer use for the environment pesticides and soil correctives. We detected increased levels in following nutrients by comparing both MR and MD mounds: phosphorus (P), sodium (Na), calcium (Ca), magnesium (Mg), total bases (TB), effective CEC (t), base saturation (V), and saturation index sodium (ISNA).